2018
DOI: 10.4103/apc.apc_130_17
|View full text |Cite
|
Sign up to set email alerts
|

Acquired ventricular septal defect due to infective endocarditis

Abstract: Acquired intracardiac left-to-right shunts are rare occurrences. Chest trauma and myocardial infection are well-known causes of acquired ventricular septal defect (VSD). There have been several case reports describing left ventricle to right atrium shunt after infective endocarditis (IE). We present here a patient found to have an acquired VSD secondary to IE of the aortic and tricuspid valves in the setting of a known bicuspid aortic valve. This is the first case reported of acquired VSD in a pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Acquired VSD secondary to IE is rare and there are only a few such cases reported [ 4 , 5 ]. This case is novel in which the patient had persistent clinical signs and symptoms of IE and subsequently developed VSD despite expedient antimicrobial therapy with resultant negative blood culture and absence of vegetation in multiple echocardiography including a TOE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquired VSD secondary to IE is rare and there are only a few such cases reported [ 4 , 5 ]. This case is novel in which the patient had persistent clinical signs and symptoms of IE and subsequently developed VSD despite expedient antimicrobial therapy with resultant negative blood culture and absence of vegetation in multiple echocardiography including a TOE.…”
Section: Discussionmentioning
confidence: 99%
“…While other strains of Staphylococcus spp. have been reported to cause IE with acquired VSD [ 5 ], to the authors’ knowledge, along with a literature review of acquired VSDs in IE, there has not been any reported case associated with PVL-producing S. aureus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genetic factors have been identified to cause VSD including chromosomal, a single gene, and polygenic inheritance. 7,8 Pinto et al 9 stated that isolated VSD accounts for 37% of all congenital heart disease in children. The incidence of isolated VSD is about 0.3% of newborns.…”
Section: Cont Table 1: Subjects Characteristicsmentioning
confidence: 99%
“…Another potential complication of IE can be the formation of ventricular septal defect due to the infection's aggressiveness which can show communication between the right ventricle and left ventricle through the membranous septum. This anatomical defect also can be figured out with a pericardium patch [15].…”
Section: Surgery Treatmentmentioning
confidence: 99%